Popular Culture in Late Imperial China - Johnson, David; Nathan, Andrew J.; Rawski, Evelyn S. (Berkeley, Los Angeles, London : University of California Press, 1985)
RAWSKI (E.S.), Economic and Social Foundations of Late Imperial Culture
JOHNSON (D.), Communication, Class, and Consciousness in Late Imperial China
HAYES (J.), Specialists and Written Materials in the Village World
HEGEL (R.E.), Distinguishing Levels of Audiences for Ming-Ch'ing Vernacular Literature
ISSEI (T.), The Social and Historical Context of Ming-Ch'ing Local Drama
WARD (B.E.), Regional Operas and Their Audiences : Evidence from Hong-Kong
BERLING (J.), Religion and Popular Culture : The management of moral capital in "The Romance of the Three Teachings"
OVERMYER (D.L.), Values in Chinese Sectarian Literature : Ming and Ch'ing "Pao-chüan"
NAQUIN (S.), The Transmission of White Lotus Sectarianism in Late Imperial China
WATSON (J.L.), Standardizing the Gods : The promotion of T'ien Hou ("Empress of Heaven")along the South China coast, 960-1960
MAIR (V.H.), Language and Ideology in the Written Popularizations of the "Sacred Edict"
LEE (L.O.F.) & NATHAN (A.J.), The Beginnings of Mass Culture : Journalism and fiction in the late Ch'ing and beyond
RAWSKI (E.S.), Problems and Prospects
bibliogr. dissém.